A Revision on the Effectiveness of Omega-3 Polyunsaturated Fatty Acids as Monotherapy in the Treatment of Major Depressive Disorder - Tommaso Accinni; Matteo Panfili; Lorenzo Tarsitani; Massimo Biondi; Massimo Pasquini; Annalisa Maraone (International Journal of Clinical Practice)
Background. Insufficient effectiveness and a difficult tolerability profile of antidepressant drugs for the treatment of major depressive disorder (MDD) have been reported, and polyunsaturated fatty acids (PUFAs) have been posited as reliable therapeutic alternatives. The present study investigated the efficacy of omega-3 PUFAs as monotherapy for MDD. Methods. Two well-trained reviewers independently looked at the most significant randomized clinical trials (RCTs) from the PubMed database regarding PUFAs’ employment in MDD compared to placebo; “major depressive disorder” and “omega-3 fatty acids,” or “omega-6 fatty acids,” or “polyunsaturated fatty acids (PUFA),” or “n − 3 polyunsaturated fatty acids,” or “eicosapentaenoic acid (EPA),” or “docosahexaenoic acid (DHA)” were used as the medical subject keywords. Results. Of the initial 96 potential RCTs based on titles and abstracts, 82 studies did not meet the inclusion criteria and were excluded. Six studies were excluded from the remaining 14 after full text revision. Eight RCTs met all the inclusion/exclusion criteria without reporting clear evidence of PUFAs’ effectiveness in the treatment of MDD. Conclusion. At present, there is no opportunity to recommend the use of omega-3 PUFAs monotherapy for the treatment of MDD, although their supplementation may be useful in some specific populations.